UPAYA MENINGKATKAN HASIL BELAJAR PPKN MELALUI METODE DISKUSI PADA MATERI KERAGAMAN BUDAYA SISWA KELAS V MI KHOIRIYATUL ULUM TEGALHARJO PATI - Isti Rohmah; Budi Tri Cahyono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The research is intended to improve the learning outcomes of Pancasila and Citizenship Education (PPKn) by applying the discussion method to  the Cultural Diversity material of grade V students of MI Khoiriyatul Ulum Tegalharjo Pati for the 2024/2025 academic year. The background of this research is because students have difficulty learning on the material, with a pre-cycle completion percentage of only 17%. The type of research to be used is the type of Class Action Research (PTK) with the Kemmis & McTaggart model which is carried out in two cycles, each of which includes the stages of planning, implementation of actions, observation, and reflection. Data collection techniques used observation, multiple-choice tests, and field notes. Data analysis was carried out in a quantitative descriptive manner. The results of the study revealed an increase in learning outcomes and student activities after the use of the discussion method. The average grade point of the class increased from 61 in the pre-cycle to 66 in cycle 1, and 75 in the second cycle. The percentage of completeness also increased significantly from 17% to 52% and finally reached 90% during cycle II. In addition to improving cognitive achievement, the use of discussion methods also encourages students' active participation during the learning process, fosters mutual respect, cooperation, and respect for cultural differences in their environment. Therefore, it can be concluded that the use of the discussion method in PPKn lessons is effectively able to improve learning outcomes, as well as foster students' tolerance towards the cultural diversity of the Indonesian nation.